Maternal serum C-reactive protein concentration and intra-amniotic inflammation in women with preterm prelabor rupture of membranes - Ivana Musilová; Marián Kacerovský; Martin Štěpán; Tomas Bestvina; Lenka Plíšková; Barbora Zedníková; Bo Jacobsson (2017)
Objective To evaluate maternal serum C-reactive protein (CRP) concentrations in pregnancies complicated by preterm prelabor rupture of membranes (PPROM) in relation to the presence of microbial invasion of the amniotic cavity (MIAC) and/or intra-amniotic inflammation (IAI). Methods Two hundred and eighty-seven women with singleton pregnancies complicated by PPROM between 2014 and 2016 were included in this study. Maternal blood and amniotic fluid samples were collected at the time of admission. Maternal serum CRP concentration was measured using a high-sensitivity immunoturbidimetric assay. Interleukin-6 (IL-6) concentration was measured using a point-of-care test. MIAC was diagnosed based on a positive polymerase chain reaction result for Ureaplasma species, Mycoplasma hominis, and/or Chlamydia trachomatis and for the 16S rRNA gene. IAI was characterized by an amniotic fluid IL-6 concentration of ≥ 745 pg/mL. Result Women with MIAC and IAI had higher maternal serum CRP concentrations than did women without (with MIAC: median 6.9 mg/L vs. without MIAC: median 4.9 mg/L; p = 0.02; with IAI: median 8.6 mg/L vs. without IAI: median 4.7 mg/L; p < 0.0001). When women were split into four subgroups based on the presence of MIAC and/or IAI, women with the presence of both MIAC and IAI had higher maternal serum CRP than did women with IAI alone, with MIAC alone, and women without MIAC and IAI (both MIAC and IAI: median: 13.1 mg/L; IAI alone: 6.0 mg/L; MIAC alone: 3.9 mg/L; and without MIAC and IAI: median 4.8 mg/L; p < 0.0001). The maternal serum CRP cutoff value of 17.5 mg/L was the best level to identify the presence of both MIAC and IAI, with sensitivity of 47%, specificity of 96%, positive predictive value of 42%, negative predictive value of 96%, and the positive likelihood ratio of 10.9. Conclusion The presence of both MIAC and IAI was associated with the highest maternal serum CRP concentrations. Maternal serum CRP concentration in women with PPROM at the time of admission can rule out the presence of the combined condition of both MIAC and IAI, therefore, it may serve as a non-invasive screening tool to distinguish between women with PPROM who are at high or at low risk for the presence of both MIAC and IAI.